Legal Protection For Doctors Against Dishonesty Of Patients In Providing Information During Covid-19 Pandemic - Ontran Sumantri Riyanto; David Maharya Ardyantara; Raditya Sri Krisnha Wardhana; Laurensius Lungan (International Journal of Science, Technology & Management, 2021)
Doctors and paramedics as health resources are the main component of health care providers to the public to achieve health development goals by national goals. Doctors and paramedics are the vanguard of treating Covid-19 patients with a very high risk of transmission of the virus. Legal protections for Doctors and paramedics are often overlooked as if society is apathetic and opinionated that it is already a duty and responsibility as medical personnel. Legal protections for the safety of Doctors and paramedics are less noticed, even though medical personnel are the vanguard in the handling of the Covid-19 pandemic. Speaking of legal protections certainly cannot be released from rights and obligations. Unprotected health workers, in this case, the profession of health workers. Violation of the rights of Doctors and paramedics related to covid-19 patient services that often occur is that the patient does not provide honest information on his condition as a Person in supervision or Patient In Supervision, so the more prone to the transmission of the Covid-19 virus that certainly has a domino effect on both doctors, Doctors and paramedics, other patients and also their families. Legal protection of Doctors and paramedics should be a serious concern of governments and hospitals. The patient must need and trained to be honest with what he feels and does. Legal protections that will surely make Doctors and paramedics feel protected in carrying out their humanitarian duties. All good measures of the assessment until evaluation will be carried out properly. Synergy together is the way to be done for all to realize quality health care.